2010
DOI: 10.1177/0963662510372313
|View full text |Cite
|
Sign up to set email alerts
|

Public understanding of the politics of global warming in the news media: the hostile media approach

Abstract: This study uses the politics of global warming in the US to investigate an affective mechanism of hostile media perception and the democratic consequences of such perception, in an effort to delineate audience and journalistic barriers to stimulating urgent concern about climate change. The study confirms that partisanship played a significant role in perceptual differences with regard to media bias in an important area of science journalism--climate change. News consumers' anger perception was tested as a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 55 publications
2
25
1
2
Order By: Relevance
“…Moreover, the relationship between hostile media perceptions and negative emotions may also be reverse, 10 though another study already found that anger itself seems not a cause of perceiving bias (Kim, 2011), which is in line with our model and findings.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the relationship between hostile media perceptions and negative emotions may also be reverse, 10 though another study already found that anger itself seems not a cause of perceiving bias (Kim, 2011), which is in line with our model and findings.…”
Section: Discussionsupporting
confidence: 82%
“…Opponents of the scientific consensus on climate changedefined here broadly as the agreement that (a) the Earth is warming and (b) most of that warming has been due to human greenhouse gas emissions (Anderegg et al, 2010;Doran and Zimmerman, 2009;Oreskes, 2004)-have often emphasized scientific uncertainty in order to forestall mitigative action (e.g., Kim, 2011;Freudenburg et al, 2008;Nisbet, 2009). Those arguments often exaggerate, for political or ideological reasons, the actual degree of uncertainty in the scientific community or imply that uncertainty justifies inaction (e.g., Hoggan and Littlemore, 2009;Jacques et al, 2008;Dunlap, 2003, 2010;Mooney, 2007;Oreskes and Conway, 2010;Stocking and Holstein, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy of information, source credibility and other issues related to messages in communication have been studied not only in disasters (Madden, ; Xie, Wang, Zhang & Yu, ) but in the general context of how people receive, perceive and process information (Carr, Barnidge, Lee & Tsang, ; Kim, ; Montanaro & Bryan, ; Young, DeSarbo & Morwitz, ). Lindell et al.…”
Section: Introductionmentioning
confidence: 99%